ANTIBACTERIAL ACTIVITY OF JAPANESE CAMBOJA (Adenium obesum) LEAF EXTRACT ON THE GROWTH OF THE BACTERI Sthaphylococcus aureus - Lestari, Widya; Kurniawan, Edy; Ustyawati, Jumari; Mentari, Ika Nurfajri (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2024)
Staphylococcus aureus bacteria are microorganisms that can causing the most common infections such as skin infections. In the treatment of infections commonly use antibiotics, but there are often problems in use of antibiotics, leading to resistance. One way Preventing resistance is by looking for alternatives that are better cheap and efficient, one example is by using frangipani plants. (Adenium obesum). Japanese frangipani leaves themselves are believed to contain alkaloids, flavonoids and saponins that function as antibacterials. The purpose of this study was to determine the effect of giving Japanese frangipani leaf extract (Adenium obesum) on the growth of Staphylococcus aureus bacteria. This research method is a laboratory experiment by means of wells diffusion with concentrations of 50%, 25%, 15% and 10%. The results of this study indicate that there is no clear zone in each concentration. The conclusion is that Japanese frangipani leaves (Adenium obesum) are unable to inhibit the growth of Staphylococcus aureus bacteria.